Is there a role for Gallium-67 SPECT in distinguishing progression and pseudoprogresion in oncologic patients receiving immunotherapy?. (2021) - Mauri, Davide; Tsiouris, Spyridon; Gkoura, Stefania; Gazouli, Ioanna; Ntellas, Panagiotis; Amylidis, Annalea; Kampletsas, Lefteris; Fotopoulos, Andreas
Abstract: Immuno-oncology (IO) with immune checkpoint inhibitors (ICIs) is the new landmark in cancer treatment. However, due to its economical-related burden and the possibility of tumor pseudoprogression with late response patterns, it is imperative to find new ways for early discrimination of patients with IO-sensitive versus IO-resistant disease. ICI-mediated antitumor responses depend on tumor immune infiltration by T-cells capable of recognizing and killing tumor cells. Nevertheless, patients may experience different responses to immunotherapy according to their tumor microenvironment and inflammatory infiltration. T-cell infiltrated tumors are referred to as 'hot' and are potential candidates for a good response to ICIs, whereas 'cold' are those tumors lacking T-cell infiltration and exhibit a narrow likelihood of response to IO therapy. Gallium-67 ( 67 Ga) scintigraphy may hold potential for separating 'hot' from 'cold' tumors, thus providing an imaging tool to distinguish 'hot' ICI-induced pseudoprogression from real early 'cold' progression. Even so, various tumors (lymphomas, lung cancer, breast cancer, hepatoma, malignant melanoma) exhibit an inherent affinity for 67 Ga that is independent of the ICI-induced immune infiltration, and this raises issues about false positivity. For that reason, future investigational studies to evaluate the prospective role of this radiotracer in the early prediction of ICI response should be confined to tumors with an inherently low 67 Ga affinity (thyroid carcinoma, gastrointestinal and genitourinary tract tumors). We describe our experience with a patient with recurrent metastatic lung adenocarcinoma under ICI therapy that was submitted to 67 Ga scanning for a fever of unknown origin and we discuss the aforementioned topics, alongside current imaging trends and future perspectives in the field.